2009
DOI: 10.1111/j.1365-2354.2008.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Benzydamine for prophylaxis of radiation-induced oral mucositis in head and neck cancers: a double-blind placebo-controlled randomized clinical trial

Abstract: We evaluated the efficacy of benzydamine oral rinse for prevention of radiation-induced mucositis. Patients with head and neck cancers, who were referred in 2004-2005, received an oral rinse of either benzydamine or placebo. One hundred patients were randomized in this trial. At the end of the study, 19 patients were excluded from the analysis because they did not use the medication for the assigned period. In the benzydamine group, the frequency of mucositis grade > or =3 was 43.6% in contrast to 78.6% in oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 3 publications
2
59
0
1
Order By: Relevance
“…Topical administration of BH as an oral rinse has been shown to be an effective and safe treatment for pharyngitis 17,18 and radiation-induced oral mucositis in patients with head and neck tumours. 19,20 Group BH = benzydamine hydrochloride treatment group; Group S = saline treatment group; PCA = patient-controlled analgesia; VATS = videoassisted thoracic surgery Previous studies have shown that BH administered as either a prophylactic oral gargle or a spray on tracheal tube cuffs reduces the incidence and severity of postoperative sore throat. 11,12,21 Moreover, pre-emptive BH application to the pharynx has been found to decrease the incidence of sore throat following the use of a laryngeal mask 22 A postoperative flexible laryngoscopic assessment of vocal cord injuries revealed that the main injuries caused by DLT intubation are redness and edema at the vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…Topical administration of BH as an oral rinse has been shown to be an effective and safe treatment for pharyngitis 17,18 and radiation-induced oral mucositis in patients with head and neck tumours. 19,20 Group BH = benzydamine hydrochloride treatment group; Group S = saline treatment group; PCA = patient-controlled analgesia; VATS = videoassisted thoracic surgery Previous studies have shown that BH administered as either a prophylactic oral gargle or a spray on tracheal tube cuffs reduces the incidence and severity of postoperative sore throat. 11,12,21 Moreover, pre-emptive BH application to the pharynx has been found to decrease the incidence of sore throat following the use of a laryngeal mask 22 A postoperative flexible laryngoscopic assessment of vocal cord injuries revealed that the main injuries caused by DLT intubation are redness and edema at the vocal folds.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was done to systematically assess the prevention and decreasing the severity of oral mucositis present in the literature regarding the treatment of oral mucositis. 10 In our study, at the end of treatment, grade I mucositis was observed in 3 (10%) and 13 (43.3%) patients of group-I and group-II respectively, Grade II mucositis was observed in 12 (40%) and 13 (43%) patients and Grade III mucositis was observed in 15 (50%) and 4 (13%) patients of group-I and group-II respectively. None of the patients developed grade IV mucositis.…”
Section: Resultsmentioning
confidence: 83%
“…Benzydamine significantly delayed the use of systemic analgesics compared with placebo as well as, effective, safe, and well tolerated for prophylactic treatment of radiation-induced oral mucositis. 9 In other study on 81-patients, Kazemian et al 10 concluded that benzydamine 0.15% oral rinse was safe and well tolerated and significantly reduced RT-induced mucositis. In the benzydamine group, the frequency of mucositis grade 3 was 43.6% in contrast to 78.6% in other group (P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Benzidamin gargaranın, eşzamanlı KT tedavisi almayan, orta doz RT (kadar 50 Gy) alan baş ve boyun kanserli hastalarda kullanımı önerilmektedir (Kanıt düzeyi 1-öneri derecesi A). [19,24] Panel, oral mukozitin önlenmesinde alkol bazlı ağız gargaralarının kullanımından kaçınılması gerektiğini belirtmektedir. Ayrıca, HKHT için yüksek doz KT alan, eşzamanlı total vücut RT uygulanan/uygulanmayan hastalarda intravenöz glutamin kullanımı (Kanıt düzeyi 2), baş ve boyun kanser tedavisi için RT uygulanan hastalarda klorheksidin gargara kullanımı (Kanıt düzeyi 2-öneri derecesi B), otolog ya da allojenik kök hücre transplantasyonu için yüksek doz KT alan hastalarda granülosit makrofaj koloni stimüle edici faktör (GM-CSF) gargara kullanımı (Kanıt düzeyi 2-öneri derecesi C); HKHT uygulanan hastalarda pentoxifylline kullanımı, RT alan hastalarda antimikrobiyal pastillerin kullanımı (Kanıt düzeyi 2-öneri derecesi B), Standart doz KT alan hastalarda Asiklovir ve benzerlerinin kullanımı (Kanıt düzeyi 2-öneri derecesi B) oral mukoziti önlemede önerilmemektedir.…”
Section: Oral Mukoziti öNlemede Kullanılan Kanıta Dayalı Uygulamalarunclassified